The rules of parenting : a personal code for bringing up happy, confident children - Templar, Richard, 1950-2006 (Pearson, 2023)
"Some parents make it look easy. They always seem to know the right things to do and say, however tricky the situation. They have a seemingly instinctive ability to raise happy, confi dent and well-balanced children. Is there something these parents know that the rest of us don't? Is it something we could all learn? The answer is a resounding YES. They know The Rules of Parenting. These Rules are the golden principles that will guide you smoothly through the everyday challenges of raising children, from siblings to discipline, from school to teens"--